Interictal plasma endothelin-1 levels do not change in individuals with episodic and chronic migraine. (July 2022) - Kim, Jiyoung; Park, Chae Gyu; Chu, Min Kyung
Background: Individuals with migraine present ictal elevation of endothelin-1 levels. Migraine can be subclassified into episodic migraine and chronic migraine. Apart from the inconsistent reports on interictal endothelin-1 levels, most studies did not distinguish between episodic migraine and chronic migraine. Methods: We measured plasma endothelin-1 levels in participants with episodic migraine (n = 87), with chronic migraine (n = 88), and controls (n = 50). Results: Interictal endothelin-1 levels were not significantly different among participants with episodic migraine, those with chronic migraine, and controls (pg/ml, median and interquartile range, 10.19 [7.76–13.69] vs. 9.25 [6.91–10.73] vs. 9.46 [7.00–14.19], p = 0.131). After excluding participants with fibromyalgia (n = 50) and medication-overuse headache (n = 21), endothelin-1 levels were still similar among groups (10.51 [7.96–14.10] vs. 9.24 [6.96–10.81] vs. 9.46 [7.00–14.19], p = 0.230). Endothelin-1 levels did not significantly differ among participants with migraine with aura, those with migraine without aura, and controls (9.36 [4.26–13.35] vs. 9.50 [7.23–13.02] vs. 9.46 [7.00–14.19], p = 0.975). There was no significant association of endothelin-1 with headache intensity (mild, 8.99 [8.99–8.99] vs. moderate, 8.71 [6.85–12.15] vs. severe, 9.55 [7.23–13.13], p = 0.517) or headache frequency per month (exponential and 95% confidence interval, 0.709 [0.296–1.698], p = 0.440) in participants with episodic migraine and chronic migraine. Conclusions: Interictal plasma endothelin-1 level is an unlikely marker for episodic migraine and chronic migraine.